Measurement of the selected spectral averaged cross sections in a radial channel of the VR-1 reactor. (December 2019) - Burianova, Nicola; Kostal, Michal; Bily, Tomas; Losa, Evzen; Simon, Jan; Schulc, Martin; Rypar, Vojtech
Abstract: The spectral averaged cross section is an important quantity used in a validation of nuclear cross section. When the cross sections are averaged over the neutron standard field ( 252 Cf(s, f) or 235 U(n, f) neutron spectrum), they can be used for tuning of evaluations. This kind of quantities is very useful because the data in integral measurements can be determined with a significantly smaller uncertainties than the standard differential data. The experiment was aimed at the spectral average cross sections measurement and was performed in a radial channel of VR-1 reactor (with fuel enrichment 19.75 wt %). The results are in a good agreement within the uncertainties with a previous measurements in LR-0 reactor (with fuel enrichment 3.3 wt %), thus it supports the hypothesis that even significant amount of 238 U(n, f) neutrons in the LR-0 reactor spectrum does not have a significant influence. The derived spectral averaged cross sections are as follows: 0.1709 ± 0.0115 mb for 89 Y(n, 2n), 10.738 ± 0.719 mb for 46 Ti(n, p), 17.896 ± 1.181 mb for 47 Ti(n, p), 0.294 ± 0.02 mb for 48 Ti(n, p), 72.994 ± 4.964 mb for 54 Fe(n, p), 0.528 ± 0.036 mb for 63 Cu(n, α), 0.444 ± 0.029 mb for 93 Nb(n, 2n) 92 Nb* and 0.239 ± 0.016 mb for 58 Ni(n, x) 57 Co. Highlights: Measurement of the spectral averaged cross sections. Irradiation in the radial channel in the VR-1 reactor. The neutron energy spectrum of the VR-1 reactor calculations. Results comparison to the IRDFF and to the LR-0 experiments.